A Multivariate Approach to Determine the Economic Profitability of Sugarcane Production Under Diverse Climatic Conditions in Brazil - Cardozo, Nilceu Piffer [UNESP]; Bordonal, Ricardo de Oliveira; Panosso, Alan Rodrigo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Springer Nature, 2020)
The prominent position of sugarcane as a source of renewable and sustainable energy resulted in the expansion of its production into regions under limiting climatic conditions, thus affecting patterns related to growth, ripening, and profitability. This study provides an assessment of the factors that compose the economic return of sugarcane production using a multivariate approach. Monthly data, including total recoverable sugars, price, productivity (for an average of five mechanized harvesting), and rainfall during seven harvest seasons (2011/2012–2017/2018), were used to perform the multivariate statistical analyses considering the climatic conditions of four regions in the state of São Paulo, southeastern Brazil (Araçatuba, Assis, Ribeirão Preto, and Piracicaba). The chosen techniques were hierarchical and non-hierarchical (k-means) cluster analysis and principal component analysis. The data indicated the existence of three groups of months that exhibited different performances: Groups I, II, and III with intermediate, high, and low gross economic returns, respectively. Although group organization presented regional variations, July, August, September, and eventually October (Group II) generally exhibited the best gross economic returns (R$5065.1 ha−1). December and November (Group III) exhibited the lowest economic returns (R$4731.5 ha−1), and April, May, and June (Group I) exhibited intermediate returns that were close to the annual average (R$4829.6 ha−1). Given the territorial extent of Brazil and the significant variations in environmental conditions, the adaptation of sugarcane cultivation and harvesting strategies to the characteristics of each producing region is fundamental for the rational and sustainable exploitation of the crop in the country.
Keywords: Biomass production; Cluster analysis; Industrial quality; Saccharum spp; Strategic planning